Equilibrium Political Budget Cycles - Rogoff, Kenneth (American Economic Review, 1990)
Political business cycle theories generally rely on nominal rigidities and voter myopia. This paper offers an equilibrium theory which preserves some basic insights from earlier models, though with significant refinements. The "political budget cycle" emphasized here is in fiscal policy rather than output and inflation; it arises via a multidimensional signal process. One can consider the welfare implications of proposals to mitigate the cycle, and the effects of altering the electoral structure.